Offsetting and Sterilization Mechanisms in Argentina (1992–2014) - Carolyn Thomas; Nicolás Cachanosky (Credit and Capital Markets – Kredit und Kapital, 2016)
We test the existence and extent of capital flows as an offset to monetary policy in Argentina from 1992–2014. After providing an analysis of Argentina"s past and current economic conditions, a theoretical framework of the offset and sterilization mechanisms will be provided. Then, with the use of VAR and IRF analysis, it is shown that a one standard deviation shock to monetary policy (measured by changes in net domestic assets) is offset between 27 %–32 % by responsive capital flows (measured by changes in net foreign assets). Furthermore, the results indicate that the Argentine government more than sterilizes shocks to capital flows through compensation of expansionary monetary policy. – – Offsetting- und Sterilisationsmechanismen in Argentinien (1992–2014) Wir testen die Existenz und das Ausmaß von Kapitalflüssen, welche in Reaktion auf Änderungen der argentinischen Geldpolitik der Jahre 1992–2014 entstanden sind und diese konterkariert haben. Nach einer kurzen Analyse der aktuellen und vergangenen ökonomischen Situation in Argentinien stellen wir ein theoretisches Modell zu Offsetting- und Sterilisationsmechanismen vor. Im Anschluss zeigen wir mit Hilfe einer IRF Analyse und einem VAR-Modell, dass eine Veränderung der Geldpolitik um eine Standardabweichung (gemessen als die Veränderung des inländischen Nettovermögens) durch entgegenwirkende Kapitalflüsse (gemessen als die Veränderung des Nettoauslandsvermögens) um 27%–32% abgeschwächt wird. Des Weiteren zeigen die Ergebnisse, dass die argentinische Regierung Kapitalverkehrsschocks durch expansive Geldpolitik nicht nur ausgeglichen sondern überkompensiert hat.
Keywords: E52; E58; F31; 330; Argentina; foreign exchange market; offset mechanism; sterilization; capital flows